Communication to the Editor—Critical Comments on “Measuring Risk on Consumer Instalment Credit” by Paul F. Smith - Cohen, Kalman J.; Hammer, Frederick S. (Management Science, 1966)
In his article [Smith, P. F. 1964. Measuring risk on consumer instalment credit. Management Sci. 11(2, November) 327–340], Smith develops a simple statistical method for measuring risk on individual accounts which he feels can be used for controlling the quality of portfolios of consumer instalment loans and for estimating loss rates. His tests seem to indicate that this approach is promising. There are, however, grave deficiencies in both the testing procedure and the conceptual foundations of his approach. To see this clearly, the more important problems that arise will be discussed in the same order as they occur in the article.